Evaluation of a Graduated Exposure Procedure to Teach Extended Mask Wearing in Various Settings to Children With Autism. Issue 5 (September 2022) - Ertel, Hallie M.; Wilder, David A.; Hodges, Ansley C.
During the COVID-19 outbreak, the Center for Disease Control (CDC) recommended that everyone 2 years and older wear a face mask while in a community setting. However, children with autism may be reluctant to wear a mask, particularly for extended durations. In the current study, we implemented a graduated exposure procedure to teach mask wearing for a minimum of 1 hour in an early intensive behavioral (EIBI) intervention clinic to three children diagnosed with autism. We subsequently probed mask wearing, and if necessary implemented the graduated exposure procedure, in each participant's home and in a mock physician's office. Finally, we collected probe data on mask wearing in another community setting and 1 month post-treatment maintenance data in the EIBI clinic. During baseline, participants wore masks for 0 second to 5 minutes. After treatment, all participants wore the mask for at least 1 hour in each setting, with maintenance probes indicating 4 to 5 hour mask tolerance.